Counter-Reformation sanctity in global and material perspective - Noyes, Ruth S. 19XX- (Sanctity in global perspective, 2025)
"This book explores the making of saints' cults in the early modern world from an interdisciplinary perspective, considering the entangled roles of materiality and globalization processes. It brings together work across diverse media, objects and materials, as well as communities, cultures and geographies to reframe a more synoptic, materials-centric and comparative history of the making and remaking of saints' cults, with special focus on the long Counter-Reformation. The contributions engage with dynamics of local and universal and draw attention to the vital role of textual, visual and material hagiographies in the creation and promotion of saints' and would-be saints' cults. The book fosters novel conceptualizations and cross-pollination of ideas across traditions, regions and disciplines, and expands hagiography's horizons by reconsidering canonical saintly figures and reframing lesser-known cults of saints and would-be saints. It will be of interest to scholars of religious and early modern history as well as art history and visual and material studies"--